2017
DOI: 10.1186/s12963-017-0128-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for anemia severity and type in Malawian men and women: urban and rural differences

Abstract: BackgroundThe global burden of anemia is large especially in sub-Saharan Africa, where HIV is common and lifestyles are changing rapidly with urbanization. The effects of these changes are unknown. Studies of anemia usually focus on pregnant women or children, among whom the burden is greatest. We describe prevalence and risk factors for anemia among rural and urban men and women of all ages in Malawi.MethodsWe analyzed data from a population-wide cross-sectional survey of adults conducted in two sites, Karong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
69
5
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 49 publications
19
69
5
5
Order By: Relevance
“…In line with other study (20), the present study reported that likelihoods of rich adult developing severe anaemia (compared to moderate, mild or non-anemic) were lower than poor adults. Such result indicates that poor adults have less access to nutritious food and fall sick more frequently as compared to the rich adults.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with other study (20), the present study reported that likelihoods of rich adult developing severe anaemia (compared to moderate, mild or non-anemic) were lower than poor adults. Such result indicates that poor adults have less access to nutritious food and fall sick more frequently as compared to the rich adults.…”
Section: Discussionsupporting
confidence: 93%
“…The present study documented that the odds of rural adults experiencing severe anaemia (against moderate, mild or non-anaemic) were higher than urban adults and this is of course congruent with other reports (19,20). The possible reasons might be rural adults more likely to have low socioeconomic status, low chance of accessing iron-rich foods and lack of adequate nutrition information as compared to urban adults (19).…”
Section: Discussionsupporting
confidence: 90%
“…The difference in the socioeconomic status, educational and occupational status of pregnant women, difference in the health service access between rural and urban areas could be the justification for the difference. Additionally, inadequate counselling by health professionals in resolving the wrong beliefs and myths regarding the iron supplementation could contribute to higher prevalence of anemia among pregnant women in rural areas [54, 55]. A study conducted in India also showed that pregnant women from the rural areas are more likely to develop anemia than women from the urban area [54].…”
Section: Discussionmentioning
confidence: 99%
“…23 Contrario a lo esperado, los datos del presente trabajo no mostraron diferencias significativas en la prevalencia de anemia según el índice de condición de bienestar. 14,24 Sin embargo, la hipótesis es que, dada la transición alimentaria en la población, actualmente existe un bajo consumo de alimentos ricos en hierro hem y un alto consumo de alimentos ricos en energía y pobres en nutrimentos; 25 no obstante, se requiere de análisis más profundos sobre la dieta para corroborar esta hipótesis.…”
Section: 21unclassified